Respuesta :
As you haven't given the options / choices for this question, I will just assume that you are meant to solve this by simplifying the expression so here I go...
SOLUTION:
= ( x + 16 ) + ( x + 24 ) + ( x + 32 )
= x + 16 + x + 24 + x + 32
Expanded Version -
= 3x + 72
Factorised Version -
= 3 ( x + 24 )
As you didn't state whether you wanted the answer to be left expanded or factorised, I have left both options above.
Hope this was helpful! :)
SOLUTION:
= ( x + 16 ) + ( x + 24 ) + ( x + 32 )
= x + 16 + x + 24 + x + 32
Expanded Version -
= 3x + 72
Factorised Version -
= 3 ( x + 24 )
As you didn't state whether you wanted the answer to be left expanded or factorised, I have left both options above.
Hope this was helpful! :)